Heidi - De Graaf, Anne; Molan, Chris; Spyri, Johanna 1827-1901. (Makati City St. Pauls, 1997)
A Swiss orphan is heartbroken when she must leave her beloved grandfather and their happy home in the mountains to go to school and to care for an invalid girl in the city.
"Original ed. published in Denmark by Scandinavia Pub. House., Copenhagen, Denmark."
Keywords: Grandfathers -- Fiction; Mountain life -- Switzerland -- Fiction; Orphans -- Fiction; Switzerland -- Fiction